Clinical Evaluation of Acupuncture as Treatment for Complications of Cerebrovascular Accidents: A Randomized, Sham-Controlled, Subject- and Assessor-Blind Trial. (20th March 2017) - Liao, Hsien-Yin; Ho, Wen-Chao; Chen, Chun-Chung; Lin, Jaung-Geng; Chang, Chia-chi; Chen, Liang-Yu; Lee, De-Chih; Lee, Yu-Chen
Abstract : Background and Purpose . The effect of acupuncture as treatment for poststroke complications is questionable. We performed a randomized, sham-controlled double-blind study to investigate it. Methods . Patients with first-time acute stroke were randomized to receive 24 sessions of either real or sham acupuncture during an eight-week period. The primary outcome measure was change in National Institute of Health Stroke Scale (NIHSS) score. Secondary outcome measures included changes in Barthel Index (BI), Instrumental Activities of Daily Living (IADL), Hamilton Depression Rating Scale (HAM-D), and Visual Analogue Scale (VAS) for pain scores. Results . Of the 52 patients who were randomized to receive acupuncture (n = 28 ) or placebo (n = 24 ), 10 patients in the acupuncture group and 9 patients in the placebo group failed to complete the treatment. In total, 18 patients in the acupuncture group and 15 patients in the control group completed the treatment course. Reduction in pain was significantly greater in the acupuncture group than in the control group (p value = 0.04). There were no significant differences in the other measures between the two groups. Conclusions . Acupuncture provided more effective poststroke pain relief than sham acupuncture treatment. However, acupuncture had no better effect on neurological, functional, and psychological improvement.